2018
DOI: 10.4103/ijoem.ijoem_43_18
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear proteins associated with noise-induced hearing loss: An update

Abstract: Noise-induced hearing loss (NIHL) is one of the major occupational disease that has influence on the quality of life of mining workers. Several reports suggest NIHL is attributed to noise exposure at workplace and approximately 16% of hearing loss is due to it. NIHL occurs as a result of exposure to high-level noise (>85 dB) in the workplace. Noise disrupts proteins present in the micromachinery of the ear that is required for mechano-electric transduction of sound waves. High-level noise exposure can lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 84 publications
(117 reference statements)
0
5
0
Order By: Relevance
“…According to the data by the World Health Organization (WHO), 16% of hearing loss among workers is caused by occupational noise [40]. Noise-induced hearing loss (NIHL) occurs as a result of exposure to noise of a high level (> 85 dB) at the workplace [8]. Negative effect of noise at work was compared in own study which showed that the vast majority of miners (approximately 80%) considered this factor as hazardous for health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the data by the World Health Organization (WHO), 16% of hearing loss among workers is caused by occupational noise [40]. Noise-induced hearing loss (NIHL) occurs as a result of exposure to noise of a high level (> 85 dB) at the workplace [8]. Negative effect of noise at work was compared in own study which showed that the vast majority of miners (approximately 80%) considered this factor as hazardous for health.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of workplaces in mining are related with physical work and exposure of workers to various health hazards on the part of such factors as: extreme temperatures, humidity, noise, vibration, and also prolonged working hours and shift work [4,6,7]. Noise at workplaces in mines is considered as the main risk factor causing hearing loss in employees [8]. Another factor unfavourable for the health of miners is coal dust.…”
Section: Introductionmentioning
confidence: 99%
“…This part of discussion aims to explore the literature surrounding the relationship between circadian rhythms, OSAS, and their association with hearing and balance disorders. [41][42][43][44][45][46][47][48][49][50][51]…”
Section: Circadian Rhythms and Osa From The Treatment Strategy Pointmentioning
confidence: 99%
“…Animal studies have demonstrated that CIH leads to hearing loss, cochlear degeneration, and disruption of the inner ear's antioxidant defense system. [47][48][49] In human studies, individuals with OSAS have shown increased prevalence of hearing loss, especially in the high-frequency range. [43][44][45][46][47][48][49][50][51] The study by Cheung et al investigated the relationship between sleep apnea syndrome and auditory evoked potentials.…”
Section: Circadian Rhythms Osas and Hearing Disordersmentioning
confidence: 99%
See 1 more Smart Citation